Perancangan E-KTP Sebagai Kunci Sepeda Motor Menggunakan Arduino - Dendy Mohammad; Muhammad Yasser Arafat (CV. Multi Kreasi Media, 2022)
Indonesia is one of the largest motorcycle producing countries. The impact of increasing motorcycle sales every year, motorcycles become the object of theft. Breaking the locks can use a T lock or demon liquid. In exposure to these problems and followed by technological developments that are getting better. Several technologies that can be initiated in motorcycle lock systems, one of which is the development of RFID (radio frequency identification). RFID has now been applied in paid toll road systems, supermarket barcodes to public transport payments. Utilization of e-KTP (Electronic Identity Card) in which there is an embedded chip and the ID can be read with RFID Tag module technology. In further development, this system module cannot be separated from using Arduino, where Arduino as a computer control tool is packaged into an IC, in its development a program must be made first. Arduino is very useful for applications that involve programming. The module that has been described is then designed a system that can secure the motorcycle. If there is a forced unlock, the Arduino will not activate the electricity contained in the motorcycle because electricity is not supplied directly to the motorcycle ignition key. The motor electrical system will turn on when Arduino identifies radio waves from the e-KTP card detected by the RFID sensor.